Knowledge and awareness of emergency contraception methods in rural and urban areas of Haryana, India - Kaur, Sukhbir Pal; Sharma, Susmita; Lata, Gagan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Emergency contraception (EC) is usage of contraceptive method after an unprotected sexual intercourse. It provides a window of opportunity for females for prevention of an unplanned pregnancy. In India, emergency contraceptive usage continues to be very poor. Thus, this study was planned to analyse the knowledge, awareness, and practices of married women in Haryana towards EC methods. Methods: This observational study was undertaken in a single centre on a section of rural and urban population in Haryana. A total of 500 women of reproductive age group were included in the study. A series of questions were asked in a face to face interview from a pre-structured questionnaire in a non-formal yet confidential environment. The data were collected, analysed, and compared with data available in literature. Results: In our study, more than 50% women had never heard of EC. Of those who were aware, majority (95.83%) knew about EC pills. IUD as EC was known to a very few women (2.08%). Television was the most common source of information followed by family and friends. The most common source of procurement of EC pills was from chemist shops (83.3%). Very few women (4.1%), knew the correct time for taking the EC pills. Conclusions: Our study affirms a poor knowledge about use of emergency contraception among women in Haryana. Imparting knowledge through television, social media and incorporating and highlighting EC use in sex education programs can greatly help to increase the awareness and knowledge of correct EC use.